A climate-water quality assessment framework for quantifying the contributions of climate change and human activities to water quality variations. (1st May 2023) - Yuan, Wang; Liu, Qiang; Song, Shuai; Lu, Yonglong; Yang, Shengjie; Fang, Zili; Shi, Zhen
Abstract: Water quality safety has attracted global attention and is closely related to the development of the social economy and human health. It is widely recognized that climate change and human activities significantly affect water quality changes. Therefore, quantifying the contributions of factors that drive long-term water quality changes is crucial for effective water quality management. Here, we built a climate-water quality assessment framework (CWQAF) based on climate-water quality response coefficients and trend analysis methods, to achieve this goal. Our results showed that the water quality improved significantly by 4.45%–20.54% from 2011 to 2020 in the Minjiang River basin (MRB). Human activities (including the construction of ecological projects, stricter discharge measures, etc.) were the main driving factors contributing 65%–77% of the improvement effect. Notably, there were differences in the contributions of human activities to water quality parameter changes, such as DO (increase (I): 0.12 mg/L, human contribution (HC): 66.8%), CODMn (decrease (D): 0.71 mg/L, HC: 67.2%), BOD5 (D: 1.10 mg/L, HC: 77.7%), CODCr (D: 4.20 mg/L, HC: 81.2%), TP (D: 0.13 mg/L, HC: 72.8%) and NH3 –N (D: 0.40 mg/L, HC: 63.0%). Climate change explained 23%–35% of the variation in water quality. The water quality response to climate change was relatively significant with precipitation. For example, the downstream region was more susceptible to climate change than was the upstream region, as the downstream movement of precipitation centers strengthened the process of climatic factors affecting water quality changes in the MRB. Generally, although human activities were the main driving factor of water quality changes at the basin scale, the contribution of climate change could not be ignored. This study provided a manageable framework for the quantitative analysis of the influence of human activities and climate change on water quality to enable more precise and effective water quality management. Graphical abstract: Image 1 Highlights: A quantitative framework (CWQAF) was developed to analyse water quality changes. CWQAF coupled climate-water quality response coefficients and trend analysis methods. Human activities were the main driver of water quality improvement. Shifting precipitation centers increased the contribution to changes in water quality. Spatially differentiated management of climate change impacts needed to be addressed.